Influence of synoptic patterns on surface ozone variability over the eastern United States from 1980 to 2012 - Shen, L.; Mickley, L. J.; Tai, A. P. K. (Atmospheric chemistry and physics, 2015)
We investigate the effect of synoptic-scale weather patterns on observed maximum daily 8-hour average (MDA8) surface ozone over the eastern United States during 1980–2012 in summer (June–August, JJA). Zonally averaged, the relative standard deviation (SD) of daily MDA8 JJA ozone shows a bimodal structure, with peaks at 28–32 and 40–45° N, and we show that those regions are most influenced by the variability in daily weather. We apply empirical orthogonal functions (EOFs) to understand the causes of this structure. The first three leading EOF patterns explain 53 % of the total variance in detrended surface ozone, displaying (1) a widespread response of ozone in the eastern United States associated with north–south movement of jet wind latitude, (2) a north–south pattern linked to the Bermuda High system when its west boundary is located along the east coast, and (3) an east–west pattern characteristic of a westward extension of the Bermuda High and an enhanced Great Plains low level jet (GPLLJ). The northern peak of ozone relative SD can be explained by polar jet activity, while the southern peak appears related to variability in the Bermuda High and GPLLJ. We define a new metric polar jet frequency as the total number of days the jet traverses the Midwest and northeast each summer. In the Midwest and northeast, we find that the correlation coefficient r between detrended mean JJA MDA8 ozone and the polar jet frequency ranges between −0.76 and −0.93 over 1980–2012 depending on the time period selected, suggesting that polar jet frequency could provide a simple metric to predict ozone variability in future climate regimes. In the southeast, the influence of the Bermuda High on mean JJA MDA8 ozone depends on the location of its west edge. For those summers when the average position of the west edge is located west of ~ 85.4° W, a westward shift in the Bermuda High west edge increases ozone in the southeast by ~ 1 ppbv deg−1 in longitude. For all summers, a northward shift in the Bermuda High west edge increases ozone over the entire eastern United States by 1–2 ppbv deg−1 in latitude. None of the synoptic patterns identified in this study show a significant trend from 1980 to 2012, confirming that the observed ozone decrease over the eastern United States during this time period is mainly caused by emission controls. Our work underscores the impact of synoptic patterns on ozone variability and suggests that a combination of changing local and synoptic meteorology together with trends in background ozone will determine the influence of climate change on US ozone air quality in future decades. The observed relationships of US surface ozone and synoptic circulations in this study can also be used to validate models of atmospheric chemistry.